O curso de licenciatura em matemática da PUC/SP e a trajetória profissional de seus egressos (2005 2010) - Silva, Daniela da (2012)
The focus of this research is based on the discussions upon the initial graduation of teachers and it takes as target of discussion the professional track analysis of the graduates of Degree Course in Mathematics from PUC/SP. It tried to identify the form of the graduates from the last five years (2005-2010), their academic and professional paths, the reasons that made them choose the Degree Course in Mathematics and their option to follow or not to follow the teaching career. It also tries to identify the activities that they are currently developing and the significance that the Degree Course had on his professional path. As theoretical and methodological it was used the contributions by Vaillant (2004, 2007, 2009), Valle (2006), Jesus (2004) and Gatti (2010) to validate the discussions and analysis about professional career and work conditions. Degree and initial training, the research used the contributions from Gatti (2009), Barreto (2009) and Dias-da-Silva (2005). It is about a qualitative research approach based on a case study. It used as instruments of data collection an initial questionnaire and exploratory interviews. In relation to teaching career, all the participants of the research weave a deep consideration and respect to the teachers of the Degree in Mathematics course and in their statements, and value the profession s nobleness, but most of them are not working as a teacher and did not pursued the career of teaching. To the graduates of the Mathematics Degree course, the highest point of the course is related to the teacher s practices and influences, and Teaching Practice, and Supervised Internship were considered the most important disciplines with highlights to the conception, organization and pace of lessons as the positive points of the course. Aspects as the lack of social valorization, represented for the low salaries, the profession s image and social prestige, the students and school conditions, the work safety, among others, seems to scare the graduates researched regarding the choice of a career in teaching